Retracted : Kritik Hukum Alasan Poligami dan Perceraian Sebab Istri Tidak Dapat Memberikan Keturunan - Anggraeni, Leni; Badruzaman, Dudi (De Jure: Jurnal Hukum dan Syari'ah, 2021)
RETRACTION TO:Leni Anggraeni and Dudi Badruzaman. â€œKritik Hukum Alasan Poligami dan Perceraian Sebab Istri Tidak Dapat Memberikan Keturunan.â€ De Jure: Jurnal Hukum dan Syar'iah 13, no. 2 (2021). https://doi.org/10.18860/j-fsh.v13i2.12905.This article has been retracted by Publisher based on the following reason:Based on an investigation from the editorial team, the author has committed an ethical violation by publishing articles with similar content in other journals. this article has publised in:Anggraeni, Leni. â€œKritik Hukum Terhadap Alasan Perceraian Dan Poligami Kaitannya Dengan Pihak Istri Yang Tidak Dapat Memberikan Keturunan.â€ Al-Intifaâ€™â€¯: Jurnal Ilmiah Ilmu Syariah 3, no. 1 (July 5, 2021): 33â€“44. http://jurnal.staisabili.net/index.php/Alintifa/article/view/17 One of the conditions of submission of a paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.